The Persuasive Language Strategies and Techniques in Political discourse: Differences and Similarities Between the United States of America and the Middle East Region in the Language of Political Speeches (مجلة المنصور, 2025)
This research article meticulously examines the persuasive language strategies and techniques employed in political speeches in both the United States of America (USA) and the Middle East region. By analyzing a diverse array of speeches delivered by prominent political figures, this study identifies key elements of rhetoric, narrative, and linguistics that characterize political discourse in these distinct regions. The analysis reveals both differences and similarities in the use of persuasive language, reflecting the unique cultural, historical, and political contexts that shape each region\'s political communication. In the realm of politics, the power of words cannot be underestimated. Political leaders harness the art of persuasive language to sway opinions, inspire action, and rally support for their causes. From stirring speeches that ignite passion to carefully crafted rhetoric that appeals to reason, the use of persuasive language strategies and techniques plays a pivotal role in shaping public perception and driving political agendas forward. In the USA, political rhetoric is often characterized by its emphasis on individualism, freedom, and democratic values. American political figures frequently invoke the nation\'s founding principles, historical narratives, and collective identity to rally support and foster a sense of national unity. Techniques such as storytelling, metaphors, and inclusive language are commonly utilized to engage and persuade audiences. Conversely, political rhetoric in the Middle East is deeply influenced by a rich tapestry of cultural, religious, and historical references. Leaders in this region often draw on religious texts, historical narratives, and cultural symbols to resonate with their audiences. Poetic language, repetition, and rhetorical questions are prevalent techniques in Middle Eastern political speeches, reflecting a tradition of oratory that values eloquence and emotional resonance.By comparing and contrasting these rhetorical approaches, this study aims to uncover the underlying factors that influence political communication in these regions. Understanding these differences and similarities can provide valuable insights into the dynamics of political discourse and the role of language in shaping public opinion. This research underscores the indispensable role of persuasive language in politics, highlighting its power to mobilize the masses, influence public perception, and shape the course of history.